A wedding in December : a novel - Shreve, Anita (New York : Little, Brown and Company, 2005)
Gathering to attend a wedding in the Berkshire Mountains of Massachusetts, seven former classmates find the reunion marked by the death of a spouse, a traumatic past event, a shocking secret, and health issues.
Keywords: Weddings -- Fiction; Domestic fiction